perancangan aplikasi layanan pernikahan get married - Riche Suwandy; Fandi Halim; Ade Hartinah; Williana Ardiyansyah (Fakultas Ilmu Komputer, Unversitas Muhammadiyah Riau, 2020)
Get Married wedding service provider application is a solution to problems that are often found in meeting the needs of marriage. Marriage needs which are a problem for the prospective newlyweds are choosing a wedding organizer, offering package prices, location of the building to hold a party, decorations. Apart from that, the problem of sightseeing marriages is also a problem that is often found because it is difficult for the bride and groom to determine the destination to be chosen. In addition, a problem that is often found is the difficulty of newlyweds to keep a wedding photo album. The Get Married application design has features to solve the problems found, including the GYF feature, which is the main feature provided by Get Married with the help of AR technology to provide an overview of the location to have a party. Then the trending feature is a feature to provide a good overview of the theme or invitation form. The package feature is the next feature that provides a solution for brides who do not have time to choose a place to hold a party, theme, because this feature is collaborated with a vendor so that the bride and groom can choose what kind of package they want.